Media Pembelajaran Video Tutorial Teknik Dasar Lempar Petanque - Komang Ayu Laksmi Saputri; I Gede Suwiwa (Mimbar Ilmu, 2022)
The lack of video-based learning materials to assist in learning petanque game tactics causes students to be less enthusiastic in participating in the learning process of basic petanque throwing techniques. The purpose of this study was to develop a learning media for the basic technique of throwing a petanque in the form of a video tutorial. This research is development research. The subjects of media validity testing include development design experts, learning content experts, and learning media experts. The subject of the trial in this study involved the students of Penjaskesrek. The data collection method in this study was a questionnaire. The data analysis technique in this research is qualitative descriptive analysis and quantitative descriptive analysis. Storyboards and screenshots of instructional video media were created as a result of this research to show the design of instructional video media. The results of the assessment by learning content experts showed a score of 85.71% with good qualifications. Assessment by learning media experts showed a score of 91.25% with very good qualifications. The results of the learning design expert assessment showed a score of 94.44% with very good qualifications. The results of individual trials showed a score of 96.66% with very good qualifications. The small group trial showed a score percentage of 93.16 with very good qualifications, and the large group trial showed a score of 90% with very good qualifications. Based on these results, it can be concluded that the video tutorial learning media developed is feasible to be applied in learning.